Enhanced Performance of DSSCs Based on the Insertion Energy Level of CdS Quantum Dots - Xiaoping Zou; Zhe Sun (Journal of Chemistry)
Cadmium sulfide (CdS) quantum dots (QDs) are assembled onto the TiO2 films by chemical bath deposition method (CBD). And the QDs size is controlled by the times of CBD cycles. They are characterized by UV-visible absorption. To avoid the photo corrosion and electrolyte corrosion, CdS and N719 are sequentially assembled onto the nanocrystalline TiO2 films to prepare a CdS/N719 cosensitized photo electrode for the dye-sensitized solar cells. In the structure of TiO2/CdS/N719 electrode, the reorganization of energy levels between CdS and N719 forms a stepwise structure of band-edge levels which is advantageous to the electron injection and hole recovery of CdS and N719 QDs. The open circuit voltage (Voc), short circuit current density (Jsc), and efficiency are increased.